Estandarización del cuidado enfermero en complicaciones postquirúrgicas de remplazo valvular aórtico en adultos - Cruz Suarez, Jean Pierre (2025)
Microorganism contamination at the surgical site is one of many factors associated with postoperative aortic valve replacement complications. The objective of the study was to develop a plan for the standardisation of nursing care in postoperative complications in patients undergoing aortic valve replacement. An exhaustive evaluation study was carried out to collect data from the sources of information: Pubmed, Scielo and Science Direct. Quantitative studies related to postoperative care in aortic valve replacement were included. This work included 4 studies, in which the nursing care of patients who were operated on by aortic valve replacement and their complications was positively addressed, where the attention of the different systems of organisms (neurological, cardiovascular, gastrointestinal, subcutaneous and renal tissue) with the different types of nursing and follow-up diagnoses is highlighted. Therefore, a plan was created to standardise nursing care for patients with aortic valve replacement complications, based on interpretations of scientific data on nursing interventions in aortic valve replacement adverse reactions in adults.